2008
DOI: 10.1111/j.1439-0434.2008.01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy of the Infection Process of Cercospora henningsii on Cassava Leaves

Abstract: Germination, penetration and sporulation of Cercospora henningsii (Allesch.) on cassava leaves were studied by scanning electron microscopy. Conidia started to germinate 9 h postinoculation producing one to two germ tubes. The germ tubes entered the leaf tissue through the abaxial surface by direct penetration of the epidermis without forming appressoria. The cassava leaf is characterized by its papillose epidermis on the abaxial surface. The penetrations occurred at smooth areas of the leaf epidermis between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
1
16
1
6
Order By: Relevance
“…Airborne isolates of these genera have been recorded in paddy fields in Bengal (India), Italy and south-western Spain (Muñoz et al 2010;Picco and Rodolfi 2002;Uddin and Chakraverty 1996); Pyricularia grisea, in particular, is reported to be highly destructive in lowland rice in temperate and subtropical Asia, Latin America, and Africa (Roy-Barman and Chattoo 2006). Cercospora henningsii has been isolated in cassava leaves by Babu et al (2009). The fungal diversity observed in the paddy-field in the present study is confirmed by the findings of Barrios and Pérez (2005), who isolated various species of Acremonium, Cladosporium, Curvularia, Drechslera and Ulocladium and Fusarium proliferatum in rice seeds in Cuba.…”
Section: Discussionsupporting
confidence: 94%
“…Airborne isolates of these genera have been recorded in paddy fields in Bengal (India), Italy and south-western Spain (Muñoz et al 2010;Picco and Rodolfi 2002;Uddin and Chakraverty 1996); Pyricularia grisea, in particular, is reported to be highly destructive in lowland rice in temperate and subtropical Asia, Latin America, and Africa (Roy-Barman and Chattoo 2006). Cercospora henningsii has been isolated in cassava leaves by Babu et al (2009). The fungal diversity observed in the paddy-field in the present study is confirmed by the findings of Barrios and Pérez (2005), who isolated various species of Acremonium, Cladosporium, Curvularia, Drechslera and Ulocladium and Fusarium proliferatum in rice seeds in Cuba.…”
Section: Discussionsupporting
confidence: 94%
“…The formation of more than one germ tube may be related to increased aggressiveness of the pathogen (Babu et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…No caso do algodoeiro, é raro observar estômatos sob as nervuras. Babu et al (2009) também relataram o mesmo fato em folhas de mandioca. A presença de conidióforos de R. areola produzindo conídios sobre a nervura leva a deduzir que esse fungo possa ter colonizado os tecidos vasculares do algodoeiro não sendo necessariamente específico para tecidos do mesófilo e ou parênquima.…”
Section: A B Cunclassified
“…Essa grande quantidade de tubos germinativos foi atribuída ao fenômeno denominado de confusão trópica, que nada mais é do que um mecanismo de resistência do hospedeiro para impedir a penetração do patógeno (Wynn, 1981). Babu et al (2007Babu et al ( , 2009, estudando os patossistemas mamona -Cercospora ricinella e mandioca -Cercospora henningsii também não observaram direcionamento dos tubos germinativos dos conídios dessas duas espécies de Cercospora para o interior dos estômatos presentes na superfície adaxial das folhas dos seus hospedeiros.…”
unclassified